The Whigs' America : Middle-Class Political Thought in the Age of Jackson and Clay - Pearson, Joseph W., 1979- (Book collections on Project MUSE., 2020)
Leading one of the two great political parties in the United States between 1834 and 1856, the Whigs battled their opponents, the Jacksonian Democrats, for offices, prestige, and power. Boasting such famous members as Henry Clay, Daniel Webster, and William Henry Seward, the party supported tariffs, banks, internal improvements, moral reform, and public education. However, because the Democrats were more successful in controlling the White House, they have received more attention from historians. This book provides a counterbalance to this trend through an attentive examination of writings from party leaders, contemporaneous newspapers, and other sources. The author explores a variety of topics, including the Whigs' understanding of the role of the individual in American politics, their perceptions of political power and the rule of law, and their impressions of the past and what should be learned from history. Throughout, he shows that the party attracted optimistic Americans seeking achievement, community, and meaning through collaborative effort and self-control in a world growing more and more impersonal. The author effectively demonstrates that, while the Whigs never achieved the electoral success of their opponents, they were rich with ideas. His detailed study adds complexity and nuance to the history of the antebellum era by illuminating significant aspects of a deeply felt, shared culture that informed and shaped a changing nation. --